KRISIS MAKNA HIDUP TOKOH KHALIL DALAM NOVEL BERPAYUNG TUHAN KARYA JAQUENZA EDEN: PERSPEKTIF LOGOTERAPI FRANKL - Asmarani Indah Kirana; U'um Qomariyah (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study examines the crisis of meaning in life experienced by the character Khalil in Jaquenza Eden’s novel, Berpayung Tuhan, through Viktor Frankl’s logotherapy perspective. The research focuses on analyzing existential crises, underlying pressures, post-death reflections, and the reconstruction of meaning. Employing a descriptive qualitative method with a psychology of literature approach, data were collected through close reading and note-taking of narratives and dialogues. The results indicate that Khalil’s crisis was triggered by failed life goals, social pressures, and an inability to find meaning in suffering, leading to an existential vacuum. The narrative’s post-death reflection serves as an evaluative space that fosters moral awareness. Meaning is reconstructed by integrating attitudinal, experiential, and creative values. This study underscores that literature not only represents existential struggles but also serves as a reflective medium for discovering life's meaning